Differential Response of Hippocampal and Cerebrocortical Autophagy and Ketone Body Metabolism to the Ketogenic Diet - Liśkiewicz, Daniela; Liśkiewicz, Arkadiusz; Nowacka-Chmielewska, Marta M.; Grabowski, Mateusz; Pondel, Natalia; Grabowska, Konstancja; Student, Sebastian; Barski, Jaroslaw J.; Małecki, Andrzej (Frontiers in Cellular Neuroscience, 2021)
Experimental and clinical data support the neuroprotective properties of the ketogenic diet and ketone bodies, but there is still a lot to discover to comprehensively understand the underlying mechanisms. Autophagy is a key mechanism for maintaining cell homeostasis, and therefore its proper function is necessary for preventing accelerated brain aging and neurodegeneration. Due to many potential interconnections, it is possible that the stimulation of autophagy may be one of the mediators of the neuroprotection afforded by the ketogenic diet. Recent studies point to possible interconnections between ketone body metabolism and autophagy. It has been shown that autophagy is essential for hepatic and renal ketogenesis in starvation. On the other hand, exogenous ketone bodies modulate autophagy both in vitro and in vivo. Many regional differences occur between brain structures which concern i.a. metabolic responses and autophagy dynamics. The aim of the present study was to evaluate the influence of the ketogenic diet on autophagic markers and the ketone body utilizing and transporting proteins in the hippocampus and frontal cortex. C57BL/6N male mice were fed with two ketogenic chows composed of fat of either animal or plant origins for 4 weeks. Markers of autophagosome formation, as well as proteins associated with ketolysis (BDH1 - 3-hydroxybutyrate dehydrogenase 1, SCOT/OXCT1 - succinyl CoA:3-oxoacid CoA transferase), ketone transport (MCT1 - monocarboxylate transporter 1) and ketogenesis (HMGCL, HMGCS2), were measured. The hippocampus showed a robust response to nutritional ketosis in both changes in the markers of autophagy as well as the levels of ketone body utilizing and transporting proteins, which was also accompanied by increased concentrations of ketone bodies in this brain structure, while subtle changes were observed in the frontal cortex. The magnitude of the effects was dependent on the type of ketogenic diet used, suggesting that plant fats may exert a more profound effect on the orchestrated upregulation of autophagy and ketone body metabolism markers. The study provides a foundation for a deeper understanding of the possible interconnections between autophagy and the neuroprotective efficacy of nutritional ketosis.